Advanced semiconductor catalyst designs for the photocatalytic reduction of CO2 - Zhangsen Chen; Gaixia Zhang; Siyi Cao; Guozhu Chen; Cuncheng Li; Ricardo Izquierdo; Shuhui Sun (Materials Reports: Energy, 2023)
Using clean solar energy to reduce CO2 into value-added products not only consumes the over-emitted CO2 that causes environmental problems, but also generates fuel chemicals to alleviate energy crises. The photocatalytic CO2 reduction reaction (PCO2RR) relies on the semiconductor photocatalysts that suffer from high recombination rate of the photo-generated carriers, low light harvesting capability, and low stability. This review explores the recent discoveries on the novel semiconductors for PCO2RR, focusing on the rational catalyst design strategies (such as surface engineering, band engineering, hierarchical structure construction, single-atom catalysts, and biohybrid catalysts) that promote the catalytic performance of semiconductor catalysts on PCO2RR. The advanced characterization techniques that contribute to understanding the intrinsic properties of the photocatalysts are also discussed. Lastly, the perspectives on future challenges and possible solutions for PCO2RR are presented.